Rural Woman Knowledge and Implementation for Practices Improving Added Value of Dairy Products through Prime Project in Beni Suef Governorate: - Gomaa, Aml Mohamed; Abu Elnaga, Mohamed Ahmed; Sakr, Mona Attia (Journal of agricultural, environmental and veterinary sciences, 2022)
This research aimed to determine respondents level of knowledge and implementation in the field of improving added value of dairy products through Prime project& identify the respondents sources of information, in addition to identify charactersistics of idea to improv added value of dairy products through (material cost- economic return- degree of complexity- possibility of experimentation) to accept it from the respondents' point of view. This research was conducted on 309 respondents who were selected randomly and systematically of participants in Prime project, Morgan and Krejcie equation had been used to determine the sample size. Data were collected by using aquestionnaire during novamber 2021, frequencies, percentages, mean, range, standard deviationwere used to present and analysis study data.The main results are as follow:Knowledge level was high 100% of practices of improvment value- added of dairy products such as cottage cheese manufacturing, cream manufacturing, butter manufacturing, and ghee manufacturing, also Implemention level was high 100% of practices of improvment value- added of dairy products such as cottage cheese manufacturing, cream manufacturing, butter manufacturing, and ghee manufacturing, the results also reveaied that most important sources of information were: rural development specialist, training courses, rural pioneer, seminars, and workshops, also the results reveaied that manufacture of the most products characterized low cost and great financial return, as it was easy to understand the recommendations of the manufacture, as well as the ease of experiment such as: cottage cheese manufacturing, cream industry, butter industry, ghee manufacturing, yogurt manufacturing and rice milk processing.
Keywords: knowledge; implementation; Practices of Improving Added Value of Dairy; Prime Project; Beni Suef Governorate